2008
DOI: 10.1002/gps.2025
|View full text |Cite
|
Sign up to set email alerts
|

Clustering and switching in semantic fluency: predictors of the development of Alzheimer's disease

Abstract: Subjects with memory complaints and AD patients have an alteration in both qualitative and quantitative aspects of semantic fluency. A clustering analysis could enhance the reliability of early AD diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 24 publications
7
47
0
3
Order By: Relevance
“…Alzheimer disease (AD) is the main cause of dementia (World Alzheimer Report 2015). It has been previously reported that abnormal performance in this specific task was associated with the occurrence of AD (Fagundo et al 2008). Thus, we suggested that this cognitive task may be more difficult to perform while walking compared to counting backward in early stages of the disease that leads to greater gait variability.…”
Section: Discussionmentioning
confidence: 73%
“…Alzheimer disease (AD) is the main cause of dementia (World Alzheimer Report 2015). It has been previously reported that abnormal performance in this specific task was associated with the occurrence of AD (Fagundo et al 2008). Thus, we suggested that this cognitive task may be more difficult to perform while walking compared to counting backward in early stages of the disease that leads to greater gait variability.…”
Section: Discussionmentioning
confidence: 73%
“…Words produced during these tasks are the result of more than one underlying cognitive process, such as “clustering” (automatic activation of one concept by a related, activated concept, making it more probable that a subject will say, “Dog, cat”) and “switching” (a deliberate, goal-oriented change from one sub-category to another, e.g . “dog… seahorse”) (Abwender, Swan, Bowerman, & Connolly, 2001; Hirshorn & Thompson-Schill, 2006; Troyer & Moscovitch, 2006; Troyer, Moscovitch, Winocur, Alexander, & Stuss, 1998; Fagundo, Lopez, Romero, Guarch, Marcos, & Salamero, 2008; Pakhomov & Hemmy, 2013). These component processes are affected in MCI and may predict conversion to dementia (Fagundo, Lopez, Romero, Guarch, Marcos, & Salamero, 2008; Murphy, Rich, & Troyer, 2006; Clark, Gatz, Zheng, Chen, McCleary, & Mack, 2009; Price, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This notion has been highlighted by studies showing that semantic fluency clustering is one of the best neuropsychological markers of focal regions affecting the temporal lobe (Troyer et al 1998). Clustering performance is also impaired in pathologies such as Alzheimer's disease, characterized by memory deficits and neurodegenerative damage to medial temporal structures (Fagundo et al, 2008;Pantel et al, 2004). Our results suggest, therefore, that the poorer semantic-based word fluency observed in ecstasy users (De Sola et al, 2008) can be explained in terms of a disorganization or a degradation of the semantic store, putatively associated with MDMA effects on hippocampus/temporal lobe functioning.…”
Section: Discussionmentioning
confidence: 96%
“…On semantic fluency, clusters were defined as groups of successively generated words that belonged to the same semantic subcategory, such as farm animals, pets, aquatic animals, African animals, and insects. The subcategories were determined a priori (Fagundo et al, 2008; for examples see also the Appendix). Cluster size was computed by adding up series of words from the same subcategory, starting from the second word within each cluster (i.e.…”
Section: Verbal Fluency Assessmentmentioning
confidence: 99%
See 1 more Smart Citation